PVDF/PEG/TiO2 Hollow Fiber Membrane for Lead(II) Removal - Putri, Shabrina Adani; Humairo, Fithri Yatul; Widiastuti, Nurul; Ong, Chi Siang; Jaafar, Juhana; Ismail, Ahmad Fauzi (IPTEK Journal of Proceedings Series, 2015)
Polyvinylidenefluoride-Polyethyleneglycol Titanium dioxide (PVDF/PEG/TiO2) mixed- matrix hollow fiber membranes were prepared via phase inversion induced by dry-jet spinning method. The composition of the dope solution were PVDF 18 gram, PEG 2 gram, N,N-dimethylacetamide (DMAc) 80 mL and TiO2 varied from 0 to 4 gram. The PVDF/PEG/TiO2 mixed-matrix hollow fiber membranes were characterised using XRD, SEM-EDX and TGA. Results indicate that TiO2 addition affects the performance of membrane such as hydrofilicity, pure water flux, porosity and antifouling properties. 2 gram TiO2 addition was found to be the optimum amount based on the results of hydrofilicity, pure water flux, porosity and antifouling properties. Furthermore, PVDF/PEG/TiO2 membranes with xx g TiO2 were used to study the adsorption of Pb(II) on the membrane at various concentration from 20-100 ppm. Results show that the membrane demonstrates good performance with best capacity adsorption of 1.512 mg/cm2 at Pb(II) concentration of 100 mg/L.